2021
DOI: 10.3390/ijms22042186
|View full text |Cite
|
Sign up to set email alerts
|

Nitrofurazone Removal from Water Enhanced by Coupling Photocatalysis and Biodegradation

Abstract: (1) Background: Environmental contamination with antibiotics is particularly serious because the usual methods used in wastewater treatment plants turn out to be insufficient or ineffective. An interesting idea is to support natural biodegradation processes with physicochemical methods as well as with bioaugmentation with efficient microbial degraders. Hence, the aim of our study is evaluation of the effectiveness of different methods of nitrofurazone (NFZ) degradation: photolysis and photodegradation in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…For the toxicity of the extracts against the tested strain, the MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) assay was implemented according to Smułek et al [ 24 ]. The changes in bacteria total cell membrane permeability were investigated with the crystal violet method described by Pacholak et al [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…For the toxicity of the extracts against the tested strain, the MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) assay was implemented according to Smułek et al [ 24 ]. The changes in bacteria total cell membrane permeability were investigated with the crystal violet method described by Pacholak et al [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…The first assay included the measurement of cell metabolic activity using the MTT indicator, similar to what is described in [ 57 ]. Further analyses included a study of changes in cell membrane permeability.…”
Section: Methodsmentioning
confidence: 99%
“…A separate issue is the bioavailability considered in the context of bioremediation of persistent organic pollutants (POPs), such as pharmaceuticals (including nitrofuran antibiotics), pesticides, and petroleum hydrocarbons. Most of the literature on their bioremediation focuses on the metabolism of these compounds, although many studies have indicated that it is the bioavailability that may in many cases determine the effectiveness of the biodegradation process [ 31 , 32 , 33 , 34 ].…”
Section: Significance Of Bioavailabilitymentioning
confidence: 99%